Amanah Saham Nasional Berhad (ASNB) / Nur Anis Ayub - Ayub, Nur Anis (Faculty of Business and Management, 2023)
The main purpose of writing this report is to elaborate and share my industrial training experience at Amanah Saham Nasional Berhad (ASNB), Seremban. In this report, I explained what is ASNB and what type of product and services that offers by this company. In general, ASNB is known as a company which operates under Permodalan Nasional Berhad (PNB) company as unit trust company. ASNB usually known as Amanah Saham Bumiputera (ASB) which is one of its fixed price funds. It is known as ASB since majority of Malaysian Bumiputera are invested on ASB. Moreover, the main focus on this report is the daily tasks given by the supervisor during my industrial training. I am super grateful to be part of ASNB Seremban even though only as an intern since I had the opportunity to learn at the bac k -office and the front-office. Two different departments that gave me a lot of lessons and experienced that can be use in the future. Moreover, a very cheerful work environment helps me to went through this industrial training program. All of team of ASNB Seremban including a cleaner, and two security guards that always be ready to help us as intern whenever needed. The opportunity to be an intern here is very recommended for all of student who needs experience before entering the real workforce.